INTEGRATING SOCIAL EXCHANGE THEORY AND ENGAGEMENT THEORY: A HOLISTIC APPROACH TO FRANCHISEE-FRANCHISOR RELATIONSHIPS - Abdul Razak Yahaya (Journal of Business Management and Accounting)
Franchisee–franchisor relationships are critical to the sustainability and success of franchise systems, influencing operational consistency and overall brand perception. This study integrates Social Exchange Theory (SET) and Engagement Theory (ET) into a unified conceptual framework that captures both transactional and relational dimensions of these relationships. Social Exchange Theory emphasizes trust, reciprocity, and fairness as foundational principles that shape mutual obligations, while Engagement Theory highlights the role of emotional and cognitive involvement as key drivers of commitment and performance. The integration of these theories offers a holistic perspective on how franchisee support services, leadership engagement, and regulatory frameworks interact to influence brand equity. The proposed framework enhances SET by incorporating emotional engagement, and extends ET through its inclusion of trust and fairness, thus bridging relational and engagement-based theoretical perspectives. Franchisee engagement is positioned as a mediating variable, while regulatory frameworks act as moderators in the enhancement of brand equity. This research employs structural equation modeling (SEM) and thematic analysis to validate the model and suggests avenues for future studies, particularly in addressing sector-specific challenges, cross-cultural dynamics, and the impact of technological innovations. The findings contribute to both theoretical advancement and practical strategies for fostering sustainable and competitive franchise ecosystems.